Antioxidant and Antimicrobial Potential of Hydroethanolic Extracts of Padina tetrastromatica from North-west Coast of India - Layana, P.; Martin Xavier, K. A.; Lekshmi, S.; Deshmukhe, Geetanjali; Nayak, B. B.; Balange, Amjad K. (Fishery Technology, 2019)
Brown seaweeds are rich sources of several biologicallyactive compounds, particularly polyphenols.The present study investigates the efficiency ofhydroalcoholic solvent to extract bioactive moleculesfrom the brown seaweed P. tetrastromatica. Sixdifferent combinations of ethanol in water (0, 20, 40,60, 80 and 100% v/v) mixture were employed toextract the bioactives with an objective to study theirantioxidant and antimicrobial activity. The antioxidantpotential of different extracts was assessed byTotal Phenolic Content (TPC), Ferric-reducing antioxidantpower (FRAP) assay, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity,2, 2'-azino-bis 3-ethylbenzothiazoline-6-sulphonicacid (ABTS) radical cation scavenging and Totalantioxidant activity assays. 100% ethanolic extractwas found to have the highest TPC and exhibitedsignificantly higher antioxidant activity for all testsdone while aqueous extract contained the highestextractive yield. The antimicrobial activity of theextracts were also evaluated against food spoilageand pathogenic bacteria using disc diffusion assay.100% extracts significantly (p